HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA DI UPTD SD INPRES LASIANA - Ede, Yovita Rilan; Koten, Angelikus N.; Kota, Martha K. (Universitas Nusa Cendana, 2024)
This study aims to: determine the relationship between Learning Motivation and Indonesian Language Learning Outcomes of grade IV students at UPTD SD Inpres Lasiana. This research uses a quantitative approach. The population of this study were all fourth-grade students at UPTD SD Inpres Lasiana with a research sample of 26 people consisting of 13 men and 13 women, the sampling technique used random sampling. Data were collected using research instruments in the form of a learning motivation questionnaire consisting of 20 questions and student learning outcomes using daily test scores and student final exams. The data analysis technique uses the normality test, homogeneity test, and correlation test. The results showed that there was a positive and significant relationship between learning motivation and Indonesian learning outcomes. The magnitude of the correlation coefficient obtained is 0.010, so the null hypothesis (H0) in this research is rejected.